Comparison of empagliflozin and sitagliptin therapy on myocardial perfusion reserve in diabetic patients with coronary artery disease. Issue 9 (September 2021) - Oh, Minyoung; Choi, Joon Ho; Kim, Seon-Ok; Lee, Pil Hyung; Ahn, Jung-Min; Lee, Seung-Whan; Moon, Dae Hyuk; Lee, Cheol Whan
Abstract : Background: Sodium-glucose co-transporter 2 inhibitors reduce the risk of cardiovascular events in type 2 diabetic patients with coronary artery disease (CAD); however, the underlying mechanisms remain unclear. Objectives: We compared the effects of empagliflozin vs. sitagliptin therapy on myocardial perfusion reserve (MPR) using dynamic single-photon emission computed tomography (SPECT) imaging. Methods: In total, 100 patients with type 2 diabetes, CAD and an MPR <2.5 were randomized to receive either empagliflozin (10 mg once daily) or sitagliptin (100 mg once daily). Dynamic SPECT examinations were performed at baseline and at 6 months. The primary endpoint was the percent change of global MPR. Evaluable SPECT data were available for 98 patients. Results: Baseline clinical characteristics and SPECT data were well balanced between the two groups. At a 6-month follow-up, the fasting glucose and glycated hemoglobin levels significantly decreased in both groups. Hematocrit and hemoglobin levels significantly increased in the empagliflozin group but not in the sitagliptin group. The global MPR significantly improved after treatment in both groups (34.5 ± 70.6%; P = 0.005 for empagliflozin vs. 22.4 ± 45.7%; P = 0.024 for sitagliptin). However, there was no significant difference in the global MPR between the two groups ( P = 0.934). Similar findings were detected with regard to the regional MPR. Conclusion: Among patients with type 2 diabetes and CAD, both empagliflozin and sitagliptin significantly improved the global MPR with no significant difference between the groups.